Strategies for student writers - Peters, Pam. (Brisbane, Qld : John Wiley and Sons, 1985)
This book is about: Writing as a means of inquiry; Essay questions; Writing to inform; Information at a glance; ...
Keywords: English language; English language -- Rhetoric; English language -- Style